The effects of alcohol dose, exposure to an in-vehicle alcohol feedback device, and subjective responses to alcohol on the decision to drink-drive in young drivers. (May 2020) - Ouimet, Marie Claude; Brown, Thomas G.; Corado, Lidia; Paquette, Martin; Robertson, Robyn D.
Highlights: Approximately 60 % of participants decided to engage in drink-driving in simulation. Perceived higher capacity to drive and male sex predicted decision to drink-drive. Higher capacity to drive predicted drink-driving for participants not exposed to alcohol feedback. Exposure to feedback disrupted the relationship between higher capacity to drive and drink-driving. Abstract: Background: Several factors may influence the decision to drink-drive (DD) in young drivers, such as the amount of alcohol consumed, exposure to an in-vehicle alcohol feedback device, and subjective responses to alcohol. Understanding of their influence on DD is lacking and may be key for targeted intervention. This randomized controlled, double-blinded, driving simulation experiment tested three main hypotheses; young drivers are more likely to engage in DD with: i) lower alcohol dose; ii) lack of exposure to an in-vehicle alcohol feedback (FB) device; and iii) lower subjective responses to alcohol intoxication (SR). Interactions between the decision to DD and SR, FB and sex were also explored. Methods: Males (n = 80) and females (n = 80) aged 20–24 years old were randomly assigned to two conditions: i) alcohol dose (0.45 g/kg or 0.65 g/kg); and ii) exposure to an in-vehicle alcohol feedback device (no or yes). Assessment of participants' SR following alcohol intake was based upon two measures: i) subjective intoxication measured by the discrepancy between an objective measure of intoxication and their subjective estimate of intoxication; and ii) perception of capacity to drive safely under alcohol (for both variables, a higher score represents lower SR). Participants were then asked to make either a negative or positive decision to DD while confronted with time-based contingencies related to their decision. Logistic regression and moderation analyses tested hypotheses. Results: Approximately 60 % of participants decided to DD. Higher odds of DD were found in participants reporting higher capacity to drive (adjusted odds ratio [ β ] = 1.03, 95 % confidence interval [CI] = 1.01–1.05) and who were males ( β   = 7.70; 95 % CI = 1.34–5.57). A main effect of either FB exposure or alcohol dose was not detected. Moderation analysis showed that lower SR, represented by higher perceived capacity to drive safely under alcohol was selectively predictive of greater likelihood of a decision to DD in participants not exposed to FB (effect = .054, p < .001, 95 % CI = .026–.083). Conclusions: Lower SR was found to be associated with a greater likelihood of the decision to DD in young drivers, while exposure to an in-vehicle FB device had no effect on DD. Importantly, FB exposure appeared to disrupt the relationship between lower SR and the decision to DD, signaling that FB may be selectively effective for young drivers possessing lower SR. Future studies are needed to clarify whether FB technology, and other interventions, can be targeted to deter DD in the young drivers most likely to benefit.